Revisiting the human uncinate fasciculus, its subcomponents and asymmetries with stem-based tractography and microdissection validation - Hau, Janice; Sarubbo, Silvio; Houde, Jean Christophe; Corsini, Francesco; Girard, Gabriel; Deledalle, Charles; Crivello, Fabrice; Zago, Laure; Mellet, Emmanuel; Jobard, Gaël; Joliot, Marc; Mazoyer, Bernard; et al. (Brain Structure and Function, 2017)
Despite its significant functional and clinical interest, the anatomy of the uncinate fasciculus (UF) has received little attention. It is known as a ‘hook-shaped’ fascicle connecting the frontal and anterior temporal lobes and is believed to consist of multiple subcomponents. However, the knowledge of its precise connectional anatomy in humans is lacking, and its subcomponent divisions are unclear. In the present study, we evaluate the anatomy of the UF and provide its detailed normative description in 30 healthy subjects with advanced particle-filtering tractography with anatomical priors and robustness to crossing fibers with constrained spherical deconvolution. We extracted the UF by defining its stem encompassing all streamlines that converge into a compact bundle, which consisted not only of the classic hook-shaped fibers, but also of straight horizontally oriented. We applied an automatic-clustering method to subdivide the UF bundle and revealed five subcomponents in each hemisphere with distinct connectivity profiles, including different asymmetries. A layer-by-layer microdissection of the ventral part of the external and extreme capsules using Klingler’s preparation also demonstrated five types of uncinate fibers that, according to their pattern, depth, and cortical terminations, were consistent with the diffusion-based UF subcomponents. The present results shed new light on the UF cortical terminations and its multicomponent internal organization with extended cortical connections within the frontal and temporal cortices. The different lateralization patterns we report within the UF subcomponents reconcile the conflicting asymmetry findings of the literature. Such results clarifying the UF structural anatomy lay the groundwork for more targeted investigations of its functional role, especially in semantic language processing.